ANALISA KEBIJAKAN PEMERINTAH TERKAIT ANCAMAN PENGANGGURAN PASCA KENAIKAN INFLASI DAMPAK PANDEMI COVID-19 - Ella, Ella; Roby Tan; Febriani Fajar Wati; Mashita Ayuni (Pusat Riset dan Inovasi Nasional, 2023)
Inflation is a condition of an increase in the price of commodity goods as a result of an economic situation that occurs in a country. Inflation has recently occurred in Indonesia, which is a follow-up impact of the Covid-19 Pandemic that has spread in Indonesia for more than 2 years. The inflation received complaints from the public because the significant increase in the price of goods made it difficult for them to meet their daily needs. What's more, many employees are threatened with layoffs because of the company's inability to pay employee salaries. This resulted in the use to make the employees. This study aims to analyze the government in dealing with policy problems as a result of rising inflation that occurred in Indonesia. The research method used is a qualitative method, with a literature study design, which is carried out by searching for data and information from various sources and previous research that supports this research. The results of the study show that the government applies various and assistance to the community as a solution to overcome post-inflation disasters, such as new jobs, promoting economic activities, and improving the skills and expertise of the workforce.